Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/779
|View full text |Cite
|
Sign up to set email alerts
|

Building Ethics into Artificial Intelligence

Abstract: As artificial intelligence (AI) systems become increasingly ubiquitous, the topic of AI governance for ethical decision-making by AI has captured public imagination. Within the AI research community, this topic remains less familiar to many researchers. In this paper, we complement existing surveys, which largely focused on the psychological, social and legal discussions of the topic, with an analysis of recent advances in technical solutions for AI governance. By reviewing publications in leading AI conferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 12 publications
0
71
0
3
Order By: Relevance
“…Zhang and Conitzer [30] showed that many classical results from Probably Approximately Correct (PAC) learning can be applied to the preference aggregation framework. For a comprehensive study of more related work 2 on AI ethics, interested readers can refer to a recent survey by Yu et al [29].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Conitzer [30] showed that many classical results from Probably Approximately Correct (PAC) learning can be applied to the preference aggregation framework. For a comprehensive study of more related work 2 on AI ethics, interested readers can refer to a recent survey by Yu et al [29].…”
Section: Related Workmentioning
confidence: 99%
“…One of the fundamental questions in AI ethics is how to allow humans to guide AI to make moral decisions when faced with ethical dilemmas. An ethical dilemma is a situation in which any decision violates certain aspects of ethics [29]. The following is a concrete example of an ethical dilemma that autonomous vehicles encounter [16].…”
Section: Introductionmentioning
confidence: 99%
“…incorporates the ethical considerations (Yu et al 2018) by prioritizing worker wellbeing considerations through recommending opportunistic rest breaks, and allowing stakeholders to influence the AI recommendations by expressing their preferences through φ and m i (t). The recommendations from CPL are given to a worker in the form of the number of tasks he should complete over a given time slot (a 0 value indicates that the worker should rest) so as to make it actionable enough for the worker to follow.…”
Section: Wrimentioning
confidence: 99%
“…From an ethically aligned design perspective (The IEEE Global Initiative on Ethics of Autonomous and Intelligent Systems 2018), it is desirable to incorporate breaks into scheduling approaches in order to prioritize workers' wellbeing. Nevertheless, as highlighted in (Yu et al 2018), ethically aligned Copyright c 2019, Association for the Advancement of Artificial Intelligence (www.aaai.org). All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…As for the ethical guidelines, the idea of teaching machines right from wrong has become an important research topic in both AI (Yu et al 2018) and in other disciplines (Wallach and Allen 2008). Much of the research at the intersection of AI and ethics falls under the heading of machine ethics, i.e., adding ethics and/or constraints to a particular system's decision making process (Anderson and Anderson 2011).…”
mentioning
confidence: 99%